Reliability measures of a cold standby system subject to refreshment - Kumar, Ajay; Garg, Reena; Barak, M. S. (International journal of system assurance engineering and management, 2023)
The continuous repair or inspection whenever required of a system made by the server is the main cause of the tiredness of the server, the refreshment is offered to the server whenever needed to enhance his performance. One unit is sufficient to operate the system out of two identical units. The main unit may fail directly, and the other unit may get failed because of remaining unused for an extended period or any other reason. The trained repairman first inspects the unit and then decides to repair or replace the unit in keeping the system operative. To simulate the model in real life it is assumed that the time for refreshment and repair policy has exponential distribution whereas the distributions of unit failure and server failure are used as arbitrary with different probability density functions. A variety of Reliability measures are explored with RPT (regenerative point technique) and semi-Markov process. To conclude the steady of this model, graphs are used corresponding to refreshment rate to show the behavior of some reliability measures such as MTSF, availability, and busy period of the server, and profit by choosing arbitrary values of the parameters.